Effect of identity as a mediator: The relationship between mathematics teacher cooperation and readiness in facing the era of industrial revolution - Zulnaidi, Hutkemri; Mafarja, Nofouz; Rahim, Suzieleez Syrene Abdul; Salleh, Umi Kalsum Mohd (Nurture, 2024)
Background: The Industrial Revolution has significantly impacted education, making mathematics instructors crucial in preparing students for the demands of the industrial era. Purpose: This research seeks to explore the correlation between mathematics teacher cooperation and readiness to face the era of the Industrial Revolution, with a specific focus on the mediating effect of identity. Design/Methodology/Approach: This research utilized a quantitative research design and collected data through surveys administered to school math instructors. The surveys assess the level of cooperation among mathematics teachers, their readiness to adapt to the challenges of the Industrial Revolution era, and their individual identities as teachers. Statistical analyses, including correlation and mediation analyses, are employed to examine the relationships among the variables. Findings: Preliminary findings indicate a positive correlation between mathematics teacher cooperation and readiness to face the Industrial Revolution era. Moreover, the mediating effect of identity suggests that a strong sense of professional identity among mathematics teachers enhances their cooperation and subsequently contributes to their readiness to adapt to the changing educational landscape. Conclusion: This research highlights the importance of fostering a strong professional identity among mathematics teachers to foster cooperation and preparedness. It provides insights for policymakers, school administrators, and educators to develop strategies to promote collaboration and professional development in the Industrial Revolution era. Contribution to Literature: This study enhances understanding of the relationship between mathematics teacher cooperation, identity, and readiness during the Industrial Revolution era, highlighting the importance of teacher identity formation.